High-power density switched reluctance machine development for high-speed spindle applications - Yasa, Yusuf; Sozer, Yilmaz; Garip, Muhammet (Tubitak Scientific & Technological Research Council Turkey, 2018)
In this study, a high-speed switched reluctance machine (HS-SRM) with cobalt-iron lamination material is proposed for spindle motors, which are used in computer numerical control machines. Wide torque-speed range, high power density, high efficiency, and low cost are the crucial issues in spindle applications. Three types of electric machine candidates, the permanent magnet synchronous machine (PMSM), induction machine (IM), and switched reluctance machine (SRM), are compared with their outstanding features. The SRM spindle motor will offer a more robust, reliable, compact, and cost-effective solution compared to the IM or PMSM spindle applications. Moreover, advancement on cobalt-iron laminations gives a chance to the SRM for competing with the PMSM and IM in terms of power density and efficiency. In this study, a high-speed SRM is designed, optimized, and analyzed. Its performance metrics are obtained based on torque-speed range and efficiency over a wide speed range. The proposed SRM is compared with existing industrial products in terms of power densities. Then the design is verified via experimental study. The results show that the HS-SRM with cobalt-iron lamination material offers ultimate power density and efficiency in wide operating conditions.
Keywords: Computer numerical control machines; high-speed applications; high-speed electric machine; milling machines; spindle motor; switched reluctance machine; DESIGN CONSIDERATIONS; LOSSES; MOTORS; Computer Science; Engineering